An Expedient Synthesis of 5-Substituted Imidazo[1,2-c]quinazolines - Korshin, Edward E.; Sabirova, Leila A.; Levin, Yakov A. (Synthesis, 2012)
An efficient three-step synthesis of 5-substituted 2,3-dihydroimidazo[1,2-c]quinazolines and imidazo[1,2-c]quinazolines was elaborated. 2-(2-Aminophenyl)-4,5-dihydro-1H-imidazole, prepared by phosphorus pentasulfide catalyzed condensation of 2-aminobenzonitrile with ethylenediamine, smoothly reacted with aldehydes to give the corresponding 2,3,5,6-tetrahydroimidazo[1,2-c]quinazolines. The CH–NH fragments of the latter were subjected to selective oxidative dehydrogenation with one equivalent of potassium permanganate on silica gel to give 2,3-dihydroimidazo[1,2-c]quinazolines. With two equivalents of potassium permanganate on silica gel, a one-pot exhaustive dehydrogenation to imidazo[1,2-c]quinazolines was accomplished.
Keywords: nitrogen heterocycles; imidazole; cyclization; oxidation; dehydrogenation; heterogeneous catalysis